IMPORTANCE OF TECHNOLOGICAL PROCESS OF PLANTING GARLIC IN UZBEKISTAN - Abdualiev, N.; Sodikov , M.; Umirzokov, J. (Educational Research in Universal Sciences, 2023)
The article presents information about the agrotechnology of garlic cultivation and its significance today. In addition, it was noted that the relevance of the process of planting garlic cloves is an important issue.